Comparison of Clinical Risk Indices for Prediction of Osteoporosis : OSTA index; KKOS Scoring System and Standard BMD Assessment in Menopause Clinic at Phrae Hospita - Ongartboon, Prakarn (Journal of Health Science of Thailand, 2018)
As osteoporosis is a main problem in menopausal women, because of a remarkable decline of estrogen. Bone Mineral Density-BMD is a standard assessment yet costly and unavailable. In that connection, clinical risk indices for prediction of osteoporosis : OSTA index for Asian women and KKOS scoring for Thai women were lately developed. The objective of this retrospective analytic study was to compare the developed clinical risk indices for prediction of osteoporosis with the standard BMD assessment. In all, 849 menopausal women attending menopausal clinic, Phrae hospital with medical record on femoral neck bone and lumbar spine by DXA (Lexxos) from the year 2006 to 2008. It was reported that sensitivities of OSTA vs KKOS for identification of femoral neck osteoporosis were 97.5 percent vs 95.1 percent and specificity of OSTA vs KKOS are 76.3 percent vs 68.6 percent and sensitivity of OSTA vs KKOS for identification of lumbar osteoporosis were 59.0 percent vs 56.9 percent and specificity of OSTA vs KKOS were 77.6 percent vs 74.9 percent. It was concluded that both clinical risk indices for prediction of osteoporosis: OSTA index; KKOS scoring system can be used for screening osteoporosis in large population where DXA is unavailable. It may become useful for holistic care in health promotion in a menopausal clinic at any primary care unit, community-based hospital, general hospital and be simple and appropriate tool for self-care to prevent osteoporosis in menopausal women and general population.